Exploration of Secondary Metabolites in Platostoma menthoides (L.) Using Ethyl Acetate Extract and Its Antibacterial, Antioxidant, and Larvicidal Activities - Pavithra Senthilkumar; Subbu Thavamurugan; Aravinth Annamalai; Prabhu Kolandhasamy; Vasanthy Muthunarayanan; Nandhini Selvaraj; Lakshmiprabha Azhagiyamanavalan; Ramachandran Vinayagam (Toxics)
Recently, there has been a growing demand for plant-based products to treat a range of health conditions. Platostoma menthoides (L.), a member of the Lamiaceae family, is widely known for its versatile therapeutic properties. The primary aim of this study is to analyze and identify the secondary metabolites found in the extract of P. menthoides obtained using ethyl acetate and to assess its antioxidant, antimicrobial, and mosquito larvicidal properties for the first time. For the chemical profiling, a GC–MS analysis of the extract was conducted, and it showed the presence of various phytoconstituents, and the FT-IR spectrum revealed the functional groups associated with them. The quantitative phytochemical estimations revealed values of 34.87 ± 0.53 mg of GAE equivalents/g and 22.19 ± 1.11 mg of QUE equivalents/g, respectively, for total phenolic and flavonoid content. The biological studies of P. menthoides extract showed potent mosquito larvicidal activity against fourth instar larvae of Aedes aegypti at a 100 µg/mL concentration with LC50 and LC90 values of 81.328 and 161.471 µg/mL, respectively. Moreover, the DPPH and FRAP radical scavenging potentials were evaluated, and the results revealed their ability to scavenge the free radicals. The extract also showed higher antibacterial effects against gram-negative bacteria when compared to gram-positive bacteria. All these findings suggest that P. menthoides is a rich source of phytoconstituents with various medicinal applications and can be used as an antioxidant, antibacterial, and mosquito-larvicidal agent.